COMPREHENSIVE ANALYSIS OF NURSING INTERVENTIONS FOR HEART FAILURE MANAGEMENT AND A FOCUS ON PATIENT EDUCATION AND SELF-MANAGEMENT STRATEGIES - 1Karimaha MukhlefAlruwaili, 2Maha Faisal Aldaweesh, 3Ghaliah Abdullah Almutairi, 4Amal Ali Alanazi, 5Najla Khalaf Almutari, 6Asma AwadAlanezi, 7Noor AwadAlanazi, 8Anwar AwadAlanazi, (Chelonian Research Foundation, 2022)
Heart failure (HF) management necessitates comprehensive nursing interventions, particularly emphasizing patient education and self-management strategies. This article provides a comprehensive audit of healthcare administrations for the administration of heart failure, including patient education and self-management techniques. The adequacy of different intercessions was assessed through a comprehensive writing audit. The method requires the extraction and collection of information. They illustrate the adequacy of nursing care in heart failure administration and are backed by charts. The Discussion delves on suggestions for honed and future investigations. This comes about to highlight the significance of clinical care and ongoing patient education in the treatment of heart failure. It is Recommendations to advance a coordinated show of persistent care to progress heart failure. Keywords: heart disappointment, nursing care, persistent instruction, self-management, care. Keywords: heart failure, nursing interventions, patient education, self-management, comprehensive care.